2007
DOI: 10.1111/j.1439-0434.2007.01258.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Study of the Alternaria solani Infection Process in Potato Cultivars with Different Levels of Early Blight Resistance

Abstract: Histopathological analyses of the infection process ofAlternaria solani were accomplished in three potato cultivars with different levels of early blight resistance. Leaflets of Aracy (resistant), Delta (moderately resistant) and Bintje (susceptible) cultivars were inoculated at the beginning of the flowering stage. In order to study the effect of leaf age, leaf samples were collected separately, in the lower, middle and upper third of the plants. Conidia germination, appressoria formation, penetration and num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 34 publications
0
20
0
1
Order By: Relevance
“…They appeared to be the first step in bacterial infection, but they were not always associated with the wilting of the plant. The progression of early steps of the infection processes is not always associated with resistance, as described in other systems (Dita et al, 2007). Indeed, specific recognition leading to defense mechanisms may initiate after penetration of the pathogen into the host tissues (Freytag et al, 1994).…”
Section: Root Symptom Development In Response To Infection Is Geneticmentioning
confidence: 94%
“…They appeared to be the first step in bacterial infection, but they were not always associated with the wilting of the plant. The progression of early steps of the infection processes is not always associated with resistance, as described in other systems (Dita et al, 2007). Indeed, specific recognition leading to defense mechanisms may initiate after penetration of the pathogen into the host tissues (Freytag et al, 1994).…”
Section: Root Symptom Development In Response To Infection Is Geneticmentioning
confidence: 94%
“…Based on these results, the authors concluded that although hypersensitive cell death is efficient against biotrophic pathogens, it does not protect plants against infection by the Oxidative burst and activity of defense-related enzymes in compatible and incompatible tomato-Alternativa solani... necrotrophic pathogens. On the contrary, Dita et al (2007) verified that the number of infection sites exhibiting HR was higher in potato plants resistant against A. solani than in the susceptible genotype after inoculation with that pathogen. They also found a relationship between the number of sites with HR and the leaf age, being the number of the penetration sites with HR higher in leaves in the upper part of the plant.…”
Section: Discussionmentioning
confidence: 81%
“…In spite of the apparent random pattern in the growth of the germ tubes, the majority of the appressoria were formed at the junctions between the epidermal cells. This has been observed by some authors in A. solani (ARAÚJO; MATSUOKA, 2004;DITA et al, 2007) and in other Alternaria species (AVELING; SNYMAN; RIJKENBERG, 1994;McROBERTS;LENNARD, 1996;BOEDO et al, 2008) infecting a variety of hosts. Hancock and Huisman (1981) suggested that the general features of leaf topography and fluctuations in the nutrient microclimate around the cell junctions could stimulate the formation of appresoria at these sites.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A spore was considered to be germinated when a germination tube was present, regardless of length or number of germ tubes per spore. All globular structures with a diameter larger than that of the germination tube or hyphae of origin were considered an appressoria(Dita et al 2007). Images of three conidia were randomly selected from a single leaf from each of four replicate plants and germ tube length was measured using Leica IM50 v4 software.…”
mentioning
confidence: 99%